FACTORS ASSOCIATED WITH SOCIAL PARTICIPATION AMONG CHINESE MIDDLE-AGED AND OLDER ADULTS POST-STROKE. (11th November 2018) - Cai, Y; Cui, D
Abstract: This study aims to examine the impact of individual-level and community-based factors on popular social participation activities of Chinese middle-aged and older adults post-stroke. Stroke survivors (2011: 413; 2013: 395; 2015: 441) recruited by the China Health and Retirement Longitudinal Study (CHARLS) were included in the analyses. As a national representative sample, less than half of participants (40% in 2011; 41% in 2015) had social participation. Between 2011 and 2015, the most popular social activities participated in were interacting with friends (range: 24.9% and 30.6%) and going to a community club to play table games (range: 14.3% and 18.0%). Females were more likely to interact with friends than males (Odds Ratio [OR]=1.56, p=0.004), stroke survivors with older age (OR=0.97, p=0.013) and lower education level (OR=0.53, p=0.009) were more likely to go to a community club to play table games. Those with impairments in activities of daily living (ADLs) (OR=7.34, p=0.009) and instrumental ADLs (OR=2.29, p=0.030) were less likely to interact with friends. Individuals that were depressed were more likely to go to a community club to play table games (OR=0.58, p=0.015). After controlling individual-level factors, we found that community-based factor (having available rooms for playing table games in the community) had different impacts on interacting with friends (OR=0.72, p<0.001) and going to a community club to play table games (OR=1.47, p<0.001). These results can help practitioners and policy makers design rehabilitation and community building plans to promote specific types of social participation.